2011
DOI: 10.1007/s12630-011-9570-y
|View full text |Cite
|
Sign up to set email alerts
|

Management of a patient with tracheomalacia and supraglottic obstruction after thyroid surgery

Abstract: Purpose We describe an unusual combination of dynamic supraglottic, glottic, subglottic, and intrathoracic airway obstructions following a total thyroidectomy. These problems were anticipated, documented videographically, and managed preemptively. Clinical features Following a total thyroidectomy, we replaced the endotracheal tube with a laryngeal mask airway, namely, the LMA-Classic TM , in a patient with symptomatic tracheal compression and probable obstructive sleep apnea. Spontaneous ventilation was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The technique was reported to be safe and allowed visualization of vocal cord movement and supraglottic structures in addition to tracheal repair. [ 25 ] Similar to this, Lee et al ,[ 29 ] in a case report, described bronchoscopic assessment through an LMA-Classic in a patient with documented supraglottic, subglottic, and intrathoracic airway obstruction following thyroidectomy. This technique confirmed tracheomalacia, which enabled early management with noninvasive continuous positive airway pressure to maintain airway patency.…”
Section: Methodsmentioning
confidence: 78%
“…The technique was reported to be safe and allowed visualization of vocal cord movement and supraglottic structures in addition to tracheal repair. [ 25 ] Similar to this, Lee et al ,[ 29 ] in a case report, described bronchoscopic assessment through an LMA-Classic in a patient with documented supraglottic, subglottic, and intrathoracic airway obstruction following thyroidectomy. This technique confirmed tracheomalacia, which enabled early management with noninvasive continuous positive airway pressure to maintain airway patency.…”
Section: Methodsmentioning
confidence: 78%
“…Tracheal rupture is usually longitudinal and is most frequently located in the pars membranosa because the posterior part of the trachea lacks cartilaginous support . However, a report on thyroid surgery has pointed out that thyroid goitre is related to tracheomalacia . Similarly, Doherty et al reported that tracheal rupture is related to the disruption of cartilaginous framework .…”
Section: Discussionmentioning
confidence: 99%
“…Cervical spinal cord injury is a rare but serious complication following a total thyroidectomy [3]. An unusual combination of dynamic supraglottic, glottic, subglottic and intrathoracic airway obstructions following a total thyroidectomy has been presented [4].…”
mentioning
confidence: 99%